2018
DOI: 10.1103/physrevd.97.076013
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous current from the covariant Wigner function

Abstract: We consider accelerated and rotating media of weakly interacting fermions in local thermodynamic equilibrium on the basis of kinetic approach. Kinetic properties of such media can be described by covariant Wigner function incorporating the relativistic distribution functions of particles with spin. We obtain the formulae for axial current by summation of the terms of all orders of thermal vorticity tensor, chemical potential, both for massive and massless particles. In the massless limit all the terms of fourt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…In [31] an ansatz of the Wigner function was proposed, taking into account the effects associated with thermal vorticity. In [8,12,13] an axial current was calculated on the basis of this Wigner function, and the resulting expression for the current exactly coincides with the standard formula for CVE. In [13] it was shown that in the expression for the mean value of the axial current, the angular velocity and acceleration play the role of additional chemical potentials, and the acceleration corresponds to an imaginary chemical potential.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In [31] an ansatz of the Wigner function was proposed, taking into account the effects associated with thermal vorticity. In [8,12,13] an axial current was calculated on the basis of this Wigner function, and the resulting expression for the current exactly coincides with the standard formula for CVE. In [13] it was shown that in the expression for the mean value of the axial current, the angular velocity and acceleration play the role of additional chemical potentials, and the acceleration corresponds to an imaginary chemical potential.…”
Section: Introductionmentioning
confidence: 88%
“…We will follow the calculation algorithm proposed in [8,25] and obtain third-order corrections in the thermal vorticity tensor. Note that according to [6,7,12,13] in the massless limit, all the terms in the axial current above third-order in the thermal vorticity tensor are canceled (at least at a temperature above Unruh temperature); therefore, there are reasons to believe that corrections above the third order will be zero for the massless case also in this method.…”
Section: Analysis Of the Effects Of Non-uniform Motion Of The Medmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the Wigner function from [22], one can calculate the mean values of different observables. In particular, in [26] and [27] a method for obtaining exact non-perturbative results is described using the example of axial current. In our case, it is necessary to calculate the energy density.…”
Section: Integral Representation and Wigner Functionmentioning
confidence: 99%
“…In our case, it is necessary to calculate the energy density. According to [26], it is necessary to decompose the energy density twice into a Taylor series…”
Section: Integral Representation and Wigner Functionmentioning
confidence: 99%